Antimicrobial Activity of Thin Solid Films of Silver Doped Hydroxyapatite Prepared by Sol-Gel Method - Simona Liliana Iconaru; Patrick Chapon; Philippe Le Coustumer; Daniela Predoi (The Scientific World Journal)
In this work, the preparation and characterization of silver doped hydroxyapatite thin films were reported and their antimicrobial activity was characterized. Silver doped hydroxyapatite (Ag:HAp) thin films coatings substrate was prepared on commercially pure Si disks by sol-gel method. The silver doped hydroxyapatite thin films were characterized by various techniques such as Scanning electron microscopy (SEM) with energy Dispersive X-ray attachment (X-EDS), Fourier transform infrared spectroscopy (FT-IR), and glow discharge optical emission spectroscopy (GDOES). These techniques have permitted the structural and chemical characterisation of the silver doped hydroxyapatite thin films. The antimicrobial effect of the Ag:HAp thin films on Escherichia coli and Staphylococcus aureus bacteria was then investigated. This is the first study on the antimicrobial effect of Ag:HAp thin films obtained by sol-gel method. The results of this study have shown that the Ag:HAp thin films with xAg=0.5 are effective against E. coli and S. aureus after 24 h.